Proximal iterated function systems using cyclic Meir-Keeler contractions and an application to fractal theory - A. Sreelakshmi Unni; V. Pragadeeswarar (Fixed Point Theory and Algorithms for Sciences and Engineering, 2025)
Abstract In this paper, we develop the proximal iterated function systems ( P I F S ) $(PIFS)$ using cyclic Meir-Keeler contractions and hence give an application in the fractal theory by constructing fractals using the new I F S $IFS$ . Furthermore, we extend the results to countable P I F S $PIFS$ .